2017
DOI: 10.1038/s41598-017-04398-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly-efficient photocatalytic degradation of methylene blue by PoPD-modified TiO 2 nanocomposites due to photosensitization-synergetic effect of TiO2 with PoPD

Abstract: Poly-o-phenylenediamine modified TiO2 nanocomposites were successfully synthesized via an ‘in situ’ oxidative polymerization method. The modified nanocomposites were characterized by BET, XRD, TEM, FT-IR, TGA, XPS, EA and UV-Vis DRS. The photocatalytic degradation of methylene blue was chosen as a model reaction to evaluate the photocatalytic activities of TiO2 and PoPD/TiO2. The results indicated that PoPD/TiO2 nanocomposites exhibited good photocatalytic activity and stability. The photocatalytic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 43 publications
6
29
0
Order By: Relevance
“…On the other hand, TiO 2 NPs prepared at pH 1.6 exhibited lower efficiency (73%) due to the electrostatic repulsion between the positively charged NPs and the cationic dye. These results are fully matched with the previously published reports 38 .
Figure 8 Photodegradation efficiencies of TiO 2 NPs prepared at different pH values; 1.6, 7.0 and 10.
…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, TiO 2 NPs prepared at pH 1.6 exhibited lower efficiency (73%) due to the electrostatic repulsion between the positively charged NPs and the cationic dye. These results are fully matched with the previously published reports 38 .
Figure 8 Photodegradation efficiencies of TiO 2 NPs prepared at different pH values; 1.6, 7.0 and 10.
…”
Section: Resultssupporting
confidence: 93%
“…The host–guest complex serves as a heterogeneous high-performance photocatalyst. Even compared to previously reported MOFs, Ru@PCC-2 has its unique advantages;25,26 first of all, the reaction does not involve any strong oxidizing agent, such H 2 O 2 , and the light source is just visible light, rather than UV light 24,27. A MOF photocatalyst ZnO@ZIF-8 achieved similar performance, but required high energy UV light (300 W high-pressure Hg lamp), instead of visible light (20 W) in our experimental setup 28.…”
Section: Resultsmentioning
confidence: 97%
“…Unlike most MOF photocatalysts, in which the frameworks contribute to the ligand-to-metal charge transfer (LMCT),24,27 PCC-2 plays the vital role of attracting both catalyst and substrates into its cavity, as well as offering the microenvironment for the reaction to take place (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…[97] reported a k app value of 7.3 × 10 −3 min −1 for photocatalytic degradation of MB after 300 min under visible light irradiation using Fe-doped TiO 2 thin films as photocatalyst. In another study, Yang et al [98] reported a k app value of 3.3 × 10 −3 min −1 for photocatalytic degradation of MB after 180 min using poly- o -phenylenediamine-modified TiO 2 nanocomposites as photocatalysts. Also, Jaihindh et al .…”
Section: Resultsmentioning
confidence: 99%